Implementasi P5 Berbasis Nilai Kearifan Lokal Pada AUD di TK Merak Ponorogo - Endang Lestari; Ahmad Pramudiyanto; Cutiana Windri Astuti (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2025)
Strengthening the Pancasila student profile is a form of activity that requires teachers to go into the field. The purpose of this study is to implement P5 activities in fostering local wisdom values ​​at Merak Kindergarten, Jalan Prahasto number 10 Surodikraman Ponorogo. The method in this study is descriptive qualitative. Data collection techniques used observation, interviews, and documentation. The results of data collection were then subjected to data reduction and analysis, data presentation and drawing conclusions. The subjects in this study were Merak Kindergarten students. In this study, it can be concluded that the implementation of P5 in fostering local wisdom in early childhood is considered very important. Through P5 activities, the values ​​of independence, mutual cooperation and global diversity can be instilled. There are five stages carried out in the implementation of P5 to foster local wisdom values, namely: recognition of regional potential, contextual, real action, reflection, and follow-up. The benefits of implementing P5 to foster local wisdom in Early Childhood Education (ECE) include: building character, fostering patriotism, developing skills, fostering an understanding of diversity, addressing teachers' limited understanding, and minimizing time and cost constraints. Key words: P5, Kearifan Lokal, AUD